Effective Coughing Technique for An.A with Ineffective Airway Clearance Due to Upper Respiratory Tract Infection in Room Cendana 3, Kardinah General Hospital, Tegal - Hana Choerunisa, Najwa; Setyo Dwi Andhini, Citra; Purbasari, Dwiyanti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Acute respiratory tract infection (ARTI) is an acute inflammation of the upper and lower respiratory tract caused by bacterial, viral, or rickettsial diseases. One of the problems that often develops in children is ARTI. Ineffective airway clearance is the inability to clear secretions or airway obstruction to maintain a patent airway. Effective coughing exercises are one of many nursing interventions that help patients with acute respiratory disorders (ARI) address poor airway clearance issues. Implementing effective coughing procedures on patient A with ineffective airway clearance due to upper respiratory tract infection at Kardinah Tegal General Hospital. Method: This study design is observational in the form of a nursing care study to explore nursing care issues in ARI with ineffective airway clearance using effective coughing techniques at Kardinah General Hospital in Tegal. The approach used is a nursing care approach that includes assessment, nursing diagnosis, planning, and implementation. Result: The study found that the effective coughing procedure had an impact on clearing the airway in Patient A with a diagnosis of acute respiratory tract infection. Conclusion: It is hoped that Patient A with an upper respiratory tract infection can perform the effective coughing procedure to clear the airway.